Imagining France as an Islamic State: Identity Construction in Michel Houellebecq’s Soumission - Mustofa, Andi (Language Circle: Journal of Language and Literature, 2020)
The regime change in France, which puts the Islamic group in a dominant position, has changed the structure of the French Republic. The dynamics of social relation transformation cause shifts in the status of social groups such as Islam, Atheists, Jews, and Catholics in social relation patterns. This descriptive qualitative research aims at revealing the form of exclusivity, resistance, and negotiation in the construction of identity performed by the characters in Soumission. The analysis is based on the concept of identity. The results of this research are the exclusive identities of Islamic group are portrayed through the education and political system and the position of women in social relation; the forms of resistance as a strategy in the construction of identity are made through demonstration, mobilization, exploitation of the body, and rejection of the use of religious symbols; the forms of negotiation are done by accepting and rejecting Islamic laws applied by the Islamic group.